Construction of novel binary metal oxides: Copper oxide–tin oxide nanoparticles regulated for selective and nanomolar level electrochemical detection of anti-psychotic drug. (1st August 2021) - Muthukutty, Balamurugan; Ganesamurthi, Jaysiva; Chen, Shen-Ming; Arumugam, Balamurugan; chang, Fu mao; Wabaidur, Saikh M.; ALOthman, Zeid A.; Altalhi, Tariq; Ali, Mohammad Ajmal
Abstract: Chlorpromazine hydrochloride (CPMH) is an anti-psychotic drug, belongs to phenothiazine derivative extensively used for psychotic disorders. Overdosage of CPMH leads to bipolar and hyperactive disorders. In this report, we designed copper oxide (CuO), tin oxide (SnO2 ), and copper oxide/tin oxide nanoparticles (CuO/SnO2 NPs) through an eco-friendly co-precipitation technique. The physicochemical properties of different metal oxides and binary metal oxide were analyzed via diverse characterization techniques. A disposable screen-printed carbon electrode (SPCE) was utilized for determining the electrochemical property and electrocatalytic activity of CuO, SnO2, and CuO/SnO2 NPs towards CPMH detection. From the results, CuO/SnO2 NPs/SPCE outcomes with lower charge transfer resistance, higher active surface area, enhanced anodic current compared to other electrodes. The excellence in the limit of detection (1 nM) of CuO/SnO2 NPs/SPCE was much beneficial compared to previously reported literature. Besides the selectivity, reproducibility, and repeatability outcomes with the satisfactory results. Moreover, the developed CuO/SnO2 NPs sensor was applied for real sample investigation in the environmental water sample, and found results deliver an accepted recovery percentage (100.08 to 102.91%). From all above analysis, it's clear that as-fabricated CuO/SnO2 NPs modified sensor was potential for electrocatalytic detection of CPMH.